Influence of Political Connections on the Relationship between Management Ability and Fraudulent Financial Reporting - Mohammad Nazaripour; Salahaldin Maghsodpour (مجله دانش حسابداری, 2020)
Objective: The quality of firm management can have a significant effect on firm value, and can provide a basis for making proper economic decisions by preparing useful reports and publishing them in the capital market. Also, political connections affect managers' motivation for financial reporting and preparing financial statements. This research aims to examine the influence of political connections on the relationship between management ability and fraudulent financial reporting in the companies listed in the Tehran Stock Exchange, Tehran Stock Exchange. Method: Regarding the purpose of this study, a sample of 158 companies listed in the TSE was selected from 2011 to 2017, and then, a data of 1106 firm-years was analyzed by a polynomial logistic regression model. Results: The findings showed that there is a negative and significant relationship between management ability and fraudulent financial reporting. Also, political connections have a significant and positive impact on the management ability and the fall of fraudulent financial reporting. Conclusion: The increased ability of management reduces the fraudulent financial reporting, and the political connections of the firm reduce the influence of the increased ability of management, aiming at reducing fraudulent financial reporting. That is, in companies with political connections, as management ability increases, fraudulent financial reporting increases. In other words, in companies with political connections, the manager's ability to reduce fraudulent reporting is weaker than the manager's ability in the fraudulent area in companies without political connections.